2005
DOI: 10.1371/journal.pgen.0030068.eor
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic recombination accelerates adaptation in the fungus Aspergillus nidulans

Abstract: Understanding the prevalence of sexual reproduction in eukaryotes is a hard problem. At least two aspects still defy a fully satisfactory explanation, the functional significance of genetic recombination and the great variation among taxa in the relative lengths of the haploid and diploid phases in the sexual cycle. We have performed an experimental study to explore the specific advantages of haploidy or diploidy in the fungus Aspergillus nidulans. Comparing the rate of adaptation to a novel environment betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 21 publications
(34 reference statements)
2
28
0
1
Order By: Relevance
“…If ruggedness appears to be a typical feature of regions of relatively high fitness, our results suggest that sex would be beneficial only for low-fitness individuals, consistent with the negative correlation between fitness and recombination rates observed for many organisms (Hadany and Beker 2003). Schoustra et al (2007) recently observed a specific advantage for mitotic recombination in the face of sign epistasis in the homothallic fungus Aspergillus nidulans. By comparing adaptation in diploid and haploid strains, they found that four diploid strains that spontaneously reverted to haploidy gained the highest fitness.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…If ruggedness appears to be a typical feature of regions of relatively high fitness, our results suggest that sex would be beneficial only for low-fitness individuals, consistent with the negative correlation between fitness and recombination rates observed for many organisms (Hadany and Beker 2003). Schoustra et al (2007) recently observed a specific advantage for mitotic recombination in the face of sign epistasis in the homothallic fungus Aspergillus nidulans. By comparing adaptation in diploid and haploid strains, they found that four diploid strains that spontaneously reverted to haploidy gained the highest fitness.…”
Section: Discussionsupporting
confidence: 87%
“…However, with the advent of genomic techniques, recent studies have begun to tackle this problem and found ample support for sign epistasis (Weinreich et al , 2006Poelwijk et al 2007; M. Salverda, F. Debets, J. van der Oost, R. Hoekstra, and A. de Visser, unpublished manuscript). Indirect support for fitness landscapes with multiple peaks has come from the analyses of fitness trajectories of evolution experiments with microorganisms, where replicate populations sometimes approach different fitness maxima (Korona et al 1994;Burch and Chao 2000;Buckling et al 2003;Schoustra et al 2007;Rozen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In particular cases, the hybridized nuclei are stable, resulting in a hybrid species with a doubled genome such as has been suggested for V. longisporum (Inderbitzin et al 2011). Parasexuality has been identified in many, mostly asexually propagating fungi during in vitro culturing and was shown to contribute to adaptive capabilities of the model fungus Aspergillus nidulans in vitro (Schoustra et al 2007). Parasexual recombination may also be involved in the exchange of effector genes between asexual lineages of V. dahliae.…”
Section: Discussionmentioning
confidence: 99%
“…Clear evidence of the evolution of evolvability comes from the fact that both mutation 59 and recombination rates 60 vary across species or clades and are influenced by the genetic makeup of an organism -they are not just passive results of external factors such as the level of background mutagenic radiation. It is also hard to deny that the makeup of the developmental system of a species -say, having an exoskeleton versus an endoskeleton -affects what sort of phenotypic space the descendants of that species can occupy.…”
Section: How Does Evolvability Evolve?mentioning
confidence: 99%